2022
DOI: 10.1007/s43546-022-00247-w
|View full text |Cite
|
Sign up to set email alerts
|

Causality analysis of the determinants of FDI in Bangladesh: fresh evidence from VAR, VECM and Granger causality approach

Abstract: We tested the causality between FDI and its determinants in Bangladesh in the presence of structural break harnessing Vector Autoregression (VAR) model and Granger causality test. Regressors such as GDP growth rate, inflation, interest, corporate tax, exchange and wage rate, and trade openness (TO) have been used. VAR model finds that interest, tax, wage, and exchange rate do not affect inward FDI. However, the inflation rate and TO significantly impact the inward FDI in Bangladesh. The Granger causality test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 106 publications
3
4
0
Order By: Relevance
“…A positive and highly significant long-run relationship between FDI and INFL is both theoretically and practically acceptable. This study has confirmed this relationship, which aligns with the recent findings obtained by [ 31 , 55 , 60 ] in the cases of Bangladesh, G20 countries, and oil-exporting countries (OPEC), respectively. Other studies by [ 43 , 54 , 63 ], have also observed that higher inflation rates attract more FDIs in BRICS and CIVETS, BRICS, and African countries, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…A positive and highly significant long-run relationship between FDI and INFL is both theoretically and practically acceptable. This study has confirmed this relationship, which aligns with the recent findings obtained by [ 31 , 55 , 60 ] in the cases of Bangladesh, G20 countries, and oil-exporting countries (OPEC), respectively. Other studies by [ 43 , 54 , 63 ], have also observed that higher inflation rates attract more FDIs in BRICS and CIVETS, BRICS, and African countries, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Our empirical finding of a positive and highly significant (p ≤ 0.01) long-run relationship between FDI and inflation in the case of GCC countries is consistent with the results of [ 30 , 31 , 55 , 60 62 ]. The phenomenon of higher inflation with higher inward FDI is widely accepted across countries, be they developing, emerging, or developed.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Foreign direct investment numbers have developed emphatically as a significant type of worldwide capital exchange over the many previous years. It is the most important economic indicator and critical component for a country's financial health and addresses a vital cause of funding capital speculation (Morshed et al, 2022). Additionally, it similarly assurances strength, as the "cold" FDI streams are viewed by way of a steadier wellspring of external financing due to its long-term stay in a country than "hot" portfolio investment treated as short period and a sentence always used for hot money is "hot money burns economy."…”
Section: Introductionmentioning
confidence: 99%